Deciphering the role of RNA structure in translation efficiency - Lin, Jianan; Chen, Yang; Zhang, Yuping; Lin, Haifan; Ouyang, Zhengqing (BMC bioinformatics, 2022)
Background RNA secondary structure has broad impact on the fate of RNA metabolism. The reduced stability of secondary structures near the translation initiation site/start codon of the coding region promotes the efficiency of translation in both prokaryotic and eukaryotic species. However, the inaccuracy of in silico folding and the focus on the coding region limit our understanding of the global relationship between the whole mRNA structure and translation efficiency. Leveraging high-throughput RNA structure probing data in the transcriptome, we aim to systematically investigate the role of RNA structure in regulating translation efficiency. Results Here, we analyze the influences of hundreds of sequence and structural features on translation efficiency in the mouse embryonic stem cells (mESCs) and zebrafish developmental stages. Our findings reveal that overall in vivo RNA structure has a higher relative importance in predicting translation efficiency than in vitro RNA structure in both mESCs and zebrafish. Also, RNA structures in 3’ untranslated region (UTR) have much stronger influence on translation efficiency compared to those in coding regions or 5' UTR. Furthermore, strong alternation between in vitro and in vivo structures in 3' UTR are detected in highly translated mRNAs in mESCs but not zebrafish. Instead, moderate alteration between in vitro and in vivo RNA structures in the 5’ UTR and proximal coding regions are detected in highly translated mRNAs in zebrafish. Conclusions Our results suggest the openness of the 3’ UTR promotes the translation efficiency in both mice and zebrafish, with the in vivo structure in 3’ UTR more important in mice than in zebrafish. This reveals a novel role of RNA secondary structure on translational regulation.